Peningkatan Kapasitas Manajerial dan Kompetensi Pedagogik Bagi Pengelola dan Fasilitator Sekolah Lansia Di DKI Jakarta - Tri Suratmi Daryanto; Dinni Agustin; Elsa Pongtuluran (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
URINDO as an Entrepreneur and Elderly Friendly University, collaborates with the DKI Jakarta Child Protection and Population Control Empowerment Service (PPAPP) and BKKBN, to mobilize people who care for the elderly to organize an elderly school that is integrated with the Elderly Family Development program (BKL). The purpose of this activity is to train health cadres, communities caring for the elderly, and PLKB officers to become managers and facilitators of schools for the elderly in 5 (five) areas of DKI Jakarta. The establishment of an elderly school requires management standards and trained learning facilitators so that they have pedagogic competence to carry out learning with an adult approach. The training methods used are brain storming, small group discussions, structured assignments and demonstrations. The result of community service activities is the formation of schools for the elderly in 5 areas of DKI Jakarta and in Kepulauan Seribu.